Nutrient management strategies to enhance Litchi production - Singh, Nav Prem; Singh, Jagdish; Kumar, Amrendra; Gill, Mandeep Singh; Gill, Bikramjit Singh (Indian Horticulture, 2021)
The widespread nutrient deficiencies can be managed with the application of the recommended dose of fertilizers that will be helpful in realizing higher litchi production in the country.